Grain Sorghum Nutrient Uptake and Yield Following Turkey Litter and Fertilizer Applications on a Claypan Soil. Issue 1 (1st December 2013) - Sweeney, Daniel W.; Pierzynski, Gary M.; Barnes, Phillip L.
Abstract : Information is limited on crop response to turkey ( Meleagris gallopavo ) litter applications on claypan soils in the eastern Great Plains. Our objectives were (i) to compare yield, yield components, and N and P nutrient uptake by grain sorghum [ Sorghum bicolor (L.) Moench] grown on a claypan soil amended with turkey litter manure and fertilizer and (ii) to compare the influence of incorporation of turkey litter by tillage to application with no tillage. The experiment was conducted from 2005 to 2007. Even though yields were low, especially in 2006, grain sorghum yielded 39 to 69% more with fertilizer and/or turkey litter applications than in the control. Turkey litter applied based on crop N needs did not improve sorghum yields above those obtained with fertilizer or with P‐based, incorporated litter. Compared with no tillage, incorporation of P‐based turkey litter increased 2‐yr (2005 and 2007) average yields and appeared to be related to improved N uptake amount and rate. Even though N‐based turkey litter applications, which overapply P, resulted in greater maximum P uptake rates, the apparent P recovery was low (7%) and the higher P uptake did not provide much additional yield. While use of turkey litter is a viable option, measured sorghum responses would not support annual, N‐based turkey litter applications, especially when environmental risks are considered.